Answer:
(f+g)(x) = 5x + 3
Step-by-step explanation:
f(x) = 2x - 6 and g(x) = 3x + 9, find (f+g)(x)
(f+g)(x) = f + g = (2x - 6) + (3x + 9) = 5x + 3
(f+g)(x) = f + g = 5x + 3
Answer:
A.
Step-by-step explanation:
If Chrustina said that and if 110 and 70 don't add up to 190 then she is wrong
Hello,
The answer to you question is 3.
27/(3+6) x 5 - 12 = 3
Hope it helps, Cheers.
Answer:
3n - 4m
Step-by-step explanation:
(2n-5m)+(n+m)
so we get this equation and from here, we expand the equation by removing the brackets, you should get:
2n-5m+n+m and just solve from here.
to make it easier, put the like terms together:
2n+n+m-5m
= 3n-4m